A mechanism to explain galaxy alignment over a range of scales. Issue 1 (5th April 2022) - Tiwari, Prabhakar; Jain, Pankaj
ABSTRACT: The observed large-scale alignment of polarization angles and galaxy axis have been challenging the fundamental assumption of homogeneity and isotropy in standard cosmology since more than two decades. The intergalactic magnetic field, and its correlations in real space, potentially seems as a viable candidate for explaining this phenomenon. It has been shown earlier that the large-scale intergalactic magnetic-field correlations can explain the alignment signal of quasars over Gpc scale, interestingly, they can also explain the radio polarization alignment observed in JVAS/CLASS data over 100 Mpc. Motivated with recent observations of galaxy axis alignment over several tens of Mpc, and Mpc scale, i.e. the cluster scale, we further explore the correlations of background magnetic field to explain these relatively small-scale alignment observations. In particular, we explore two recently claimed signals of alignment in the radio sources in the FIRST catalogue and in the ACO clusters. We find that the FIRST alignment signal is well-explained in terms of the intergalactic magnetic field with a spectral index of −2.62 ± 0.03. Furthermore, the model also partially explains the very small scale alignment (alignment within clusters). Though the elementary model proposed in this work seems to have its limitations at very small scales, the large-scale magnetic-field correlations potentially seem to explain the polarization and galaxy axis alignment from Gpc to Mpc scales.